2009
DOI: 10.1371/journal.pone.0006744
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and Postnatal Nutritional Histories Influence Reproductive Maturation and Ovarian Function in the Rat

Abstract: BackgroundWhile prepubertal nutritional influences appear to play a role in sexual maturation, there is a need to clarify the potential contributions of maternal and childhood influences in setting the tempo of reproductive maturation. In the present study we employed an established model of nutritional programming to evaluate the relative influences of prenatal and postnatal nutrition on growth and ovarian function in female offspring.MethodsPregnant Wistar rats were fed either a calorie-restricted diet, a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 64 publications
7
145
2
3
Order By: Relevance
“…For instance in the rat, maternal caloric restriction during pregnancy led to early pubertal onset of offspring [65]. We cannot measure the influence of ROS utero on age at first reproduction of female reindeer because this life-history trait is unknown for most of them.…”
Section: Discussionmentioning
confidence: 99%
“…For instance in the rat, maternal caloric restriction during pregnancy led to early pubertal onset of offspring [65]. We cannot measure the influence of ROS utero on age at first reproduction of female reindeer because this life-history trait is unknown for most of them.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding an obesogenic diet to female rats before mating and through lactation has also been shown to lead to maternal obesity as well as hyperphagia, increased adiposity, decreased muscle mass, reduced locomoter activity and accelerated puberty in the offspring. 57 Samuelsson et al 58 have also shown that offspring from pregnant rats fed with a 'junk food diet' of 16% fat and 33% sugar throughout pregnancy and lactation exhibited higher blood pressure, greater adiposity and insulin resistance in comparison with control offspring. There were also persistent alterations in the expression of PPARg2, 11b-hydroxysteroid dehydrogenase type I and the b2 and b3 adrenoreceptors in adipose tissue of the offspring, which may lead to increased adipogenesis and decrease lipolysis in these rats.…”
Section: The Developmental Origins Of Human Metabolic Diseasementioning
confidence: 98%
“…Maternal food restriction (Leonhardt et al, 2003;Iwasa et al, 2010) or uterine artery ligation (Engelbregt et al, 2000) are associated with late vaginal opening or first estrus. Some authors have reported no effect of maternal food restriction on pubertal development while a single study (Sloboda et al, 2009) found an acceleration of pubertal onset. Such discrepancies could be due to differences in food restriction, birth weight or postnatal weight gain.…”
Section: Abnormal Energy Availability and Timing Of Puberty: Mechanismentioning
confidence: 98%